A Public Service? Mediatization of the Olympic Games in Croatia and Slovenia. (September 2022) - Ličen, Simon; Antunovic, Dunja; Bartoluci, Sunčica
The Olympic Games are the largest mediated sporting mega-event, and broadcasters are instrumental in ensuring their exposure and financial viability. In the digital era, the Olympics navigate technological and societal changes that contest the values of sport, carry political and economic implications, and shape the relationship between the organizers and nation states. These interdependencies vary by global regions. This study examines the mediatization of sport as manifested in digital Olympic content published on Facebook during the Tokyo Olympics by public service media (PSM) in Croatia and Slovenia—two countries inconsistently assigned to either Central and Eastern Europe or Southeast Europe. These PSM face a host of challenges, including rising media rights costs, digitalization, and political interference, while continuing to broadcast the Olympics. On their Facebook pages, contest-related updates were the primary type of content, general news and especially human interest content was rare, critical posts were virtually non-existent, and "home" athletes were politicized conspicuously. Mediatization in this region seems delayed, facilitates event-focused and decontextualized sport content, and appears central in promoting patriotic narratives. On social media, broadcasters perpetuate problematic practices characteristic of sport media and only partially fulfill the roles traditionally ascribed to PSM.